Penyelesaian Sengketa Konsumen Dengan Pelaku Usaha Di Luar Pengadilan Dalam Perspektif Undang-Undang Perlindungan Konsumen - Zanariyah, Sri (Universitas Sang Bumi Ruwa Jurai, 2024)
The use of products from the results of a business from business actors, not all of them are in accordance with the wishes of consumers, this can even cause losses on the part of consumers, resulting in disputes between consumers and business actors. Therefore this study aims to find out, understand and explain the settlement of disputes that occur between consumers and business actors. Dispute resolution can be done in court and can also be done outside the court, so researchers need to determine the focus of research, in this case the settlement carried out outside the court. The imposition of sanctions against the wrong party is not only in the field of civil law, but can also be given criminal sanctions, so it is necessary to conduct research on the imposition of these criminal sanctions. This research is research in the field of law, the approach method uses an approach to laws and regulations governing consumer protection, especially related to legal principles. -the parties to the dispute take peaceful steps to realize a fast, inexpensive and simple trial, so that the rights and obligations of both parties can be fulfilled together. The existence of criminal sanctions in consumer disputes is due to the many actions that can be carried out by business actors that can harm consumers in general (society in general), not just consumers who have become victims